Construction of a memory battery for computerized administration, using item response theory - Ferreira, A. I.; Almeida, L.; Prieto, G. (Psychological Reports, 2012)
In accordance with Item Response Theory, a computer memory battery with six tests was constructed for use in the Portuguese adult population. A factor analysis was conducted to assess the internal structure of the tests (N = 547 undergraduate students). According to the literature, several confirmatory factor models were evaluated. Results showed better fit of a model with two independent latent variables corresponding to verbal and non-verbal factors, reproducing the initial battery organization. Internal consistency reliability for the six tests were alpha = .72 to .89. IRT analyses (Rasch and partial credit models) yielded good lnfit and Outfit measures and high precision for parameter estimation. The potential utility of these memory tasks for psychological research and practice will be discussed.